#TITLE_ALTERNATIVE# - (NIM : 20511303) ; Pembimbing Dr. Achmad Rochliadi, M.Si, Prof. Dr. I Made Arcana, MULTAZAM
Batteries are a portable energy suppliers. Is one of them rechargeable and electrolyte polymer membrane-based lithium ion battery. This research is going to study the performance of commercial and chitosan-lithium battery cells. The battery used in this study was PLH-1RO3F-type polymer lithium battery with capacity of 620 mAh and voltage of 3.7 volt. The separator on commercial battery was displaced by chitosan lithium that was made as electrolyte polymer membrane with addition of 15% LiClO4. Chitosan was isolated from shrimp shell waste. The conductivity of chitosan lithium membrane was found to be 1.25 x 10-4 S cm-1. Performance analysis of commercial and chitosan-lithium battery cell was done using Vencon UBA5 with variations of charge and discharge currents. It is found that the highest effective capacity percentage of 93.63% was obtained by 0,2C charge and 0.5C discharge current. The highest energy efficiency was 95.4% given by the battery with 0.7C charge and 0.3C discharge current. Impedance spectroscopy shown that the Resr decreases with decrease of constant discharge current. Higher currents (2C and 1C) gave higher resistances compared to lower currents (0.5C and 0.3C). Chitosan-lithium battery cell gave different results compared to commercial battery, in which effective capacity and energy efficiency decreases with decreasing discharge current with very small percentage compared to commercial battery cell. The highest effective capacity and energy efficiency, respectively are 12.55% and 16.58% and it were obtained by the battery with 0.2C charge and 1C discharge current. Resr of chitosan-lithium battery tends to decrease with decreasing discharge current on 1C charge current, while it tends to increase on 0.7C and 0.2C charge current on decreasing discharge current and membrane conductivity decreased to 1.37 x 10-4 S cm-1 after charging/discharging test.